The Political Economy of Resource Management in Nigeria: Governance, Accountability, and Sustainable Development - Gbadebo, Adedeji (UIN Sunan Gunung Djati Bandung, 2025)
This study investigates the political economy of resource management in Nigeria, with an emphasis on governance, accountability, and sustainable development. It tries to understand how, despite Nigeria's immense natural resource riches, systemic governance failings, elite capture, and inadequate accountability frameworks continue to perpetuate poverty. Using a qualitative technique, the study examines secondary data from government reports, policy papers, and academic literature, augmented by text analysis, to find recurring themes in Nigeria's resource governance dynamics. The study is based on Rational Choice Theory (RCT), which states that political and economic actors prioritize self-interest, resulting in actions that perpetuate corruption, mismanagement, and unequal resource distribution. The findings highlight Nigeria's entrenched rentier state structure, in which more than 80% of national oil wealth supports elite patronage networks, undermines institutional accountability, and stifles economic diversification. Vested interests have hampered reforms such as the Petroleum Industry Act (2021) and the Nigerian Extractive Industries Transparency Initiative (NEITI), resulting in few benefits for disadvantaged communities such as the oil-rich Niger Delta. Environmental degradation caused by oil spills and gas flaring, along with chronic poverty (63% multidimensional poverty), highlights the human and ecological consequences of ineffective government. Despite diversification attempts, Nigeria is mired in the